2011
DOI: 10.1021/jf200323c
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherol Concentration in Almond Oil: Genetic Variation and Environmental Effects under Warm Conditions

Abstract: The concentration of the different tocopherol homologues in almond kernel oil was determined in 17 almond cultivars grown in two different experimental orchards, in Spain and Morocco. The three main homologues showed a large variability, ranging from 210.9 to 553.4 mg/kg of oil for α-tocopherol, from 4.64 to 14.92 mg/kg for γ-tocopherol, and from 0.2 to 1.02 mg/kg for δ-tocopherol. The year effect was significant, independent of the experimental site, for all homologues and total tocopherol, the values of α-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
47
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 23 publications
13
47
1
Order By: Relevance
“…Differences between the two cultivars were already evident by chemical analysis, with protein and lipid content comparable to that previously reported [15,17,18]. The most striking difference was the total phenol content (10 times higher in the FCcv than in CAcv).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Differences between the two cultivars were already evident by chemical analysis, with protein and lipid content comparable to that previously reported [15,17,18]. The most striking difference was the total phenol content (10 times higher in the FCcv than in CAcv).…”
Section: Discussionsupporting
confidence: 84%
“…Thus, the consumption of almonds is gaining interest locally and worldwide. Factors such as the almond genotype [14,15], the growing region [16,17], the climatic conditions during the growing season [18], the harvest time [19], the storage conditions might influence the chemical J Gastrointestin Liver Dis, March 2018 Vol. 27 No 1: [31][32][33][34][35][36][37][38][39] composition of almonds and their nutraceutical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Merr.) oil (Almonor et al 1998), shea butter (a commercial seed fat of the shea tree, Vitellaria paradoxa Gaertner) (Maranz and Wiesman 2004), and olive (Olea europaea) oil (Romero et al 2003) and by genotype, geographic location, and year in almond (Kodad et al 2011). This is the first study which compares the tocopherol content in Brazil nuts from different geographic areas.…”
Section: Discussionmentioning
confidence: 99%
“…kernels of four cultivars were evaluated, where the prevalent vitamer was g-tocopherol, and a statistical analysis of the obtained results was also conducted to define these profiles as a reliable indicator of a specific variety (Barreira et al 2009). Kodad et al (2011) determined the concentration of different tocopherol homologues in almond (Prunus amygdalus Batsch) kernel oil in 17 almond cultivars. In this case, the year and location effects as well as the genotype were significant, and the authors suggested that these effects could not be explained by the temperature differences between sites, but possibly by other environmental factors such as rainfall and irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Its consumption has beneficial effects on human health, and is specially related to the lipid profile in the blood and the risk of cardiovascular diseases (Chen et al, 2006;Jenkins Virgin almond oil: Extraction methods and composition • 3 et al, 2006), although it also benefits the intestinal transit, reduces blood pressure, prevents anemia and cancer, protects against free radicals, etc (Spiller et al, 1998;Kodad et al, 2011). On the negative side, the potential allergic reaction of susceptible individuals to some protein compounds can present a risk associated with almond consumption (Chen et al, 2006).…”
Section: Almond: a Nut With High Comercial And Nutritional Valuementioning
confidence: 99%